2017
DOI: 10.1530/erc-16-0512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ThyroSeq v2 performance in thyroid nodules with indeterminate cytology

Abstract: ThyroSeq v2 claims high positive (PPV) and negative (NPV) predictive values in a wide range of pretest risks of malignancy in indeterminate thyroid nodules (ITNs) (categories B-III and B-IV of the Bethesda system). We evaluated ThyroSeq v2 performance in a cohort of patients with ITNs seen at our Academic Cancer Center from September 2014 to April 2016, in light of the new diagnostic criteria for non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP). Our study included 182 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 20 publications
9
109
2
1
Order By: Relevance
“…Oncogene panels are generally considered rule‐in tests, although more recent panels like ThyroSeq version 2 (University of Pittsburgh Medical Center, Pittsburgh, PA) also claim rule‐out ability . In our experience, this panel seemed reliable as rule‐out test in follicular neoplasms but not in atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) . Besides the need to bring the performance of oncogene panels into sharper focus, their role in planning the extent of surgery is controversial and needs to be defined .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Oncogene panels are generally considered rule‐in tests, although more recent panels like ThyroSeq version 2 (University of Pittsburgh Medical Center, Pittsburgh, PA) also claim rule‐out ability . In our experience, this panel seemed reliable as rule‐out test in follicular neoplasms but not in atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) . Besides the need to bring the performance of oncogene panels into sharper focus, their role in planning the extent of surgery is controversial and needs to be defined .…”
Section: Introductionmentioning
confidence: 85%
“…A 7‐gene panel that looked for 14 point mutations in 4 genes ( BRAF , HRAS , KRAS , and NRAS ) and 3 rearrangements ( PAX8/PPARG , RET/PTC1 , and RET/PTC3 ), was used in 102 nodules (miRInform; Asuragen, Austin, TX, in 101 of them) until September 2014 . ThyroSeq version 2 that searches for >1000 hotspots in 14 genes ( AKT1 , BRAF , CTNNB1 , GNAS , HRAS , KRAS , NRAS , PIK3CA , PTEN , RET , TP53 , TSHR , TERT , and EIF1AX ) and 42 gene fusions ( ALK , BRAF , IGF2BP3 , NTRK1 , NTRK3 , PPARG , and RET ) was used thereafter in 190 nodules . The change of the panel was based on hypothetical improved performance for our institutional pretest risk of malignancy .…”
Section: Methodsmentioning
confidence: 99%
“…lence 18. This high probability of cancer-free survival for negative results is consistent with a test that effectively rules out the need for surgery.In our study, we examined the impact of reflex microRNA testing not only when nodules lacked mutations but also when nodules had weak driver mutations, given their association with both benign and malignant disease [11][12][13][14][15]. This high probability of cancer-free survival for negative results is consistent with a test that effectively rules out the need for surgery.In our study, we examined the impact of reflex microRNA testing not only when nodules lacked mutations but also when nodules had weak driver mutations, given their association with both benign and malignant disease [11][12][13][14][15].…”
mentioning
confidence: 84%
“…ThyroSeq was developed using next-generation sequencing to identify point mutations and gene fusions commonly present in thyroid cancers. Thyroseq v2 targeted 14 genes and 42 gene fusion products, with an initial reported sensitivity and specificity of >90% (1,2). Independent validation studies confirmed the high negative predictive value but reported lower positive predictive values (3).…”
Section: Introductionmentioning
confidence: 96%